Automotive vehicle assembly processes and operations management - Tang, He (Society of Automotive Engineers. Electronic publications., 2017)
Proven technologies and processes are explored in this examination of modern automotive manufacturing. Fundamentals and applications, as well as new advances are discussed as the author bridges the gap between academic research and industrial practice. Each chapter includes review questions and research topics.